2010
DOI: 10.1603/ec09432
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Seven <I>Bacillus thuringiensis</I> Cry Proteins Against <I>Cylas puncticollis</I> and <I>Cylas brunneus</I> (Coleoptera: Brentidae) Using a Novel Artificial Diet

Abstract: "Sweetpotato weevils" Cylas puncticollis (Boheman) and Cylas brunneus F. (Coleoptera: Brentidae) are the most important biological threat to sweetpotato, Ipomoea batatas L. (Lam), productivity in sub-Saharan Africa. Sweetpotato weevil control is difficult due to their cryptic feeding behavior. Expression of Cylas-active Bacillus thuringiensis (Bt) Cry proteins in sweetpotato could provide an effective control strategy. Unfortunately, Bt Cry proteins with relatively high toxicity against Cylas spp. have not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…The sweet potato weevil is the major sweet potato insect pest worldwide, however, only three reports on transformed plants with insecticidal genes cowpea trypsin inhibitor, snowdrop lectin genes and cryIII gene have been published thus far [17,18,31]. Also, it is known that Bt is widely used in pest control agents, especially highly activate against lepidopteran pests.…”
Section: Biological Test Resultsmentioning
confidence: 99%
“…The sweet potato weevil is the major sweet potato insect pest worldwide, however, only three reports on transformed plants with insecticidal genes cowpea trypsin inhibitor, snowdrop lectin genes and cryIII gene have been published thus far [17,18,31]. Also, it is known that Bt is widely used in pest control agents, especially highly activate against lepidopteran pests.…”
Section: Biological Test Resultsmentioning
confidence: 99%
“…Craveiro et al (2010) reported the efficient biological control of sugarcane giant borer caused by the Lepidopteran larvae Telchin licus licus (Castniidae) by variants of Cry1Ia toxins. Other studies reported the high toxicity of B. thuringiensis Cry protein towards Anthonomus grandis Boheman (Coleoptera: Curculionidae) (de Souza Aguiar et al, 2012) and towards Cylas puncticollis and Cylas brunneus (Coleoptera: Brentidae) (Ekobu et al, 2010).…”
Section: Insecticidal Activity Of B Thuringiensis Derived Biopesticidesmentioning
confidence: 98%
“…A number of the Etx/Mtx2 family of Cry toxins are also reported to require a binary partner for full activity. Cry23Aa (also known as ET33) acts with Cry37 (ET34) and has activity against various coleopteran insects Ekobu et al, 2010). Cry15Aa and Cry33Aa form binary partnerships with two other proteins (40kDa and NT32KD respectively) that, due to their lack of individual activity, have not been assigned Cry names, and share no obvious sequence similarity with any other characterized protein (Kim et al, 2003;Naimov et al, 2011).…”
Section: Sphaericus B Thuringiensis Bacillus Cereus and Paenibamentioning
confidence: 99%